German Operetta on Broadway and in the West End, 1900-1940 - Scott, Derek B. (Humanities, 2019)
A study of a neglected but crucial part of the history of the West End and Broadway. The stage works presented here connect to major topics of the twentieth century including modernity, cosmopolitanism and media technology. This book is also available as Open Access on Cambridge Core.